Persistent inequalities in global air quality monitoring should not delay pollution mitigation - E. Keith Smith; Camille Fournier de Lauriere; Ella Henninger (Proceedings of the National Academy of Sciences, 2025)
Air pollution is a global health crisis that disproportionately affects lower- and middle-income countries. We examine global air quality monitoring data, highlighting persistent inequalities in high-exposure regions, and assess the potential of emerging technologies to improve data utility for mitigation. Improving air quality, however, does not need to wait for more data, nor will monitoring alone drive action. Immediate mitigation measures with broad cobenefits are needed now to reduce pollution, even in data-scarce settings.